Мathematical Simulation of Electromagnetic Parameters of Single Infinite Long Grounding Electrodes at Flowing of Alternating Power Current - D. A. Gerasimovich; E. A. Dziaruhina (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The paper presents results of a mathematical simulation of electromagnetic parameters of single lengthy grounding electrodes (electrode rod resistance, resistance against grounding alternating current flowing in the ground and grounding electrode voltage) at flowing of alternating power current. Approximate analytical expressions for calculation of the stated grounding electrode parameters are proposed in the paper.